Stress-protective effects of micronized progesterone in treatment of anxiety disorders in pregnant women after in vitro fertilisation - Natalya I. Tapilskaya; Mikhail S. Nekrasov; Inna O. Krikheli; Ksenia V. Ob'edkova; Alexander M. Gzgzyan; Igor Y. Kogan; Ruslan I. Glushakov (IP Berlin A.V., 2021)
Aim. To study a stress-protective efficacy of micronized progesterone (MP) in pregnant women with anxiety disorders after in vitro fertilisation (IVF). Materials and methods. We conducted a prospective, comparative open-label randomized trial in two IVF-clinics. A total of 98 pregnant women after IVF with anxiety disorders were recruited at the 9th week of pregnancy. Progesterone supplementation after IVF for luteal phase support was administered out until 9 weeks gestation. Then, after randomization, group 1 (n=35) received 400 mg per day of MP vaginally, group 2 (n=33) received 400 mg of MP orally, group 3 (n=30) was comparative for the other groups. The duration of progesterone treatment was 12 weeks. The Spielberger State Trait Anxiety Inventory (STAI), the Montgomerysberg depression rating scale (MADRS), Hospital Anxiety and Depression Scale (HADS), and the Epworth Sleepiness Questionnaires (ESQ) were used to compare maternal mood at 9 weeks (day of randomization) after delivery and at 283, 565, 847 days after randomization. Results. The mean STAI sumscore in MP-groups was significantly lower than in group 3 starting from day 565 and continued until the end of the study. There were no significant differences between vaginal and oral administration of progesterone. There were no significant differences between the mean sumscores when questioning on the HADS, MADRS and ESQ. Conclusion. Prolonged use of MP in pregnant women with anxiety disorders led to the prevention of manifestations of an increase in anxiety and depression. The stress-protective and neuromodulating properties of MP can determine additional indications for its prolonged administration in women with anxiety disorders and/or premorbid history.